Association of biofilm formation with multi drug resistance in clinical isolates of Pseudomonas aeruginosa - Abdulhaq, Nazia; Nawaz, Zeeshan; Zahoor, Muhammad Asif; Siddique, Abu Baker (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Pseudomonas aeruginosa is considered as foremost cause of hospital acquired infections due to its innate and plasmid mediated resistance to multiple antibiotics making it a multi drug resistant (MDR) pathogen. Biofilm formation is a pathogenic mechanism harbored by this pathogen which further elevates its resistance to antibiotics and host defense system. The aim of the present study was to evaluate the biofilm forming potential and distribution of pslA gene in multi drug resistant Pseudomonas aeruginosa isolates obtained from different clinical samples. A total of 200 different clinical samples were collected after obtaining written consent from the patients. The samples were subjected to isolation and identification of P. aeruginosa by standard microbiological procedures. Confirmation of isolates was done by polymerase chain reaction targeting oprL gene. Kirby Bauer method was performed for detection of MDR isolates. Congo red agar (CRA) test and Microtiter plate assay (MPA) for observing the biofilm forming ability and amplification of pslA gene was also performed on MDR isolates. The results showed that from 200 samples 52 (26 %) were P. aeruginosa and among them 20 (38.46 %) were MDR isolates. The CRA showed 23 (44.23 %) while MPA detected 49 (94.23 %) isolates as biofilm producers while all the MDR isolates showed biofilm formation by MPA method. The pslA gene was detected in all biofilm forming isolates while 90 % in MDR P. aeruginosa. It was concluded that biofilm forming P. aeruginosa are more resistant to tested antibiotics and biofilm formation is strongly associated with presence of pslA gene.
EXCLI Journal;Vol. 19 2020, p 201-208
Keywords: Multidrug resistance; Biofilm formation; Pseudomonas aeruginosa; pslA gene; 610